(untitled) (Research, Society and Development, 2022)
This investigation was carried out from the analysis of students’ knowledge in the daily life of the teacher/student in the classroom, related to the sociocultural and labor context of the students of PROEJA (National Program for Integration of Professional Education with Young and adult Education) - Campus in Castanhal at the Federal Institute of Pará – IFPA. It is also based on the qualitative approach, since is concerned with the particularities of the reality produced in the time/school/community interaction. Semi-structured questionnaires were also used as data collet technique, assigned to teachers, students, and coordinator of the Course. Thus, based on the perceptions of teachers, students and PROEJA coordinator, it was found that the Education of Youth and Adults discusses the experiences and knowledge of these students in the teaching-learning process. The results showed that the Pedagogy of Alternating Cycle, applied in this teaching modality achieved its objective: to promote constant knowledge sharing between the students’ living environment, articulating practice and theory in different times and spaces such as school/community, therefore, it is based on a pedagogical proposal that it produces dialogue, integration, and sociocultural relations, which develop the formative process in different social spaces.